Fare Evasion and Monopoly Regulation - Martin Besfamille; Nicolás Figueroa; León Guzmán (Center for Economic Studies and ifo Institute (CESifo), 2022)
We consider the regulation of a monopoly facing consumers that may evade payments, an important issue in public utilities. To maximize total surplus, the regulator sets the price and socially costly transfers, ensuring that the monopoly breaks-even. With costly effort, the firm can deter evasion. Under unit demand and fixed quality, price is independent of marginal cost, but increasing in the marginal cost of public funds. When quality is endogenous, we find sufficient conditions that imply a non-monotonic relation between price and marginal cost of public funds. We extend the model to consider non-unit demand and moral hazard.
Keywords: D42; H20; L43; L51; 330; regulation; natural monopoly; evasion; marginal cost of public funds